Strategies of Regency Adiwiyata (Green) School Management at Secondary Education Level in Sintang Regency - Daniel Murdani; Abdul Hakim; Bagyo Yanuwiadi (Indonesian Journal of Environment and Sustainable Development, 2018)
This study aims to identify the strengths, weaknesses, opportunities and threats (SWOT)  and formulate coaching strategy of Adiwiyataschools in Sintang Regency. A qualitative descriptive method with IFAS and EFAS analysis technique were used. The results shows dominant strengths factor including vision, mission and objectives that are environmentally sound in Adiwiyata school team. Meanwhile dominant weakness factor involves the limited budget allocation for Adiwiyata development. The dominant factor of opportunity and threat including ability in followingcompetencies in other activities in the field of environment and mutations of school principals or teachers, respectively. Adiwiyata regency school positions based on IFAS and EFAS analysis are in quadrant II (23,-5). Thus the coaching strategy includes (1) capacity building, skills and knowledge of Adiwiyata team through seminars and training funded by local government; (2) Budget allocation proportionally for supporting activities of Adiwiyata both from schools and local government that is regularly enrolled every year; (3) Vision, mission and school objectives must accommodate local wisdom of the community in protecting the environment; (4) school principal and teacher mutations should consider tracking not on a pragmatic basis. To realize the coaching strategy needs to be done continuous cooperation between the schools with various stakeholders so as to increase the predicate Adiwiyata at a higher level.Keywords: Coaching strategy, Regency Adiwiyata, School management, Sintang Regency